The Ngaben Ceremony: Contextualizing Character Formation in Social Science Education - Komang Surya Adnyana (Indonesian Values and Character Education Journal, 2025)
Ngaben as a form of social activity resulting from religious and cultural practices, not only has a theological dimension. However, it has pedagogical substance. The essentialism of ngaben values, which are rich in socio-cultural values, can be systematically accommodated in social science education. Social science education that examines aspects of social life can use ngaben as a contextual aspect in instilling character values in students. The purpose of this research is to interpret the socio-cultural activities within ngaben as a primary aspect in shaping student behavior, because it contains ethical values. The ethical values obtained through contextual learning experiences are the result of the interpretation and implementation of social meaning. Additionally, the inclusivity of socio-cultural activities can also reshape constructive discourse in the classroom. The research on the ngaben ceremony in shaping character education in social studies learning uses a qualitative approach, specifically a case study. The stages of the case study in this research are operationalized in several aspects, namely: a) case selection, b) literature review, c) formulation of the problem focus, d) data collection, e) data analysis. The collectivity in the preparation of the ceremony can be seen in the mebat process. Ngaben also has a local value substance called ngayah, which represents the sincerity of a social community in helping other members of society. The ngaben ceremony and the ngayah system represent social integration, due to the context of social science learning materials and character building. Furthermore, ngaben also has a constructive aspect in forming values of responsibility (social solidarity) in social studies education. In conclusion, the values of the ngaben ceremony in the contextualization of social studies learning include social integration values and responsibility values. The implementation of ngaben is not only theologically dimensional, but the practice of Hinduism can also be pedagogically contextualized.